“Técnicas de Estimulación en el Desarrollo de la Tonicidad Muscular en los Niños y Niñas de 4 años de Educación Inicial de la Unidad Educativa Hualcopo Duchicela, Parroquia Columbe, Periodo 2015-2016”. - Marcatoma Guamán, Reveca (2017)
This research is about stimulation techniques in the development of muscular tone in children of 4 years of 11gc in pre-school are Hualcopo Duchicela Educational Institution, corresponding to Columbe district, during the 2015-2016 school year. lt was important from the beginning to be clear of 1 the level of muscular tone of the children on order lo apply the corresponding techniques. The objective of the present study is to determine if stimulation techniques allow for the development of muscle tone in the children. Firstly, the problem was raised. then the objectives, both general and specific, The research was based on the scientific and theoretical component, in which it was possible to clarify the variables, These mention that early stimulation techniques help children grow all ages. It is also important to mention that tonic activity is indispensable to develop movements that is regulated by the nervous system. In addition, the definition of basic terms and table of variables were elaborated. The research methodology was non-experimental, type of research: exploratory level of research: diagnostic and exploratory, 100 percent of the population was used, that is lo say 27 children. An observation sheet was applied which allowed for the interpretation of the data, the analysis of the results and they elaboration of conclusions and recommendations. Additionally, a bibliography, a webgraphy and attachments were included.